Implementation of Marriage Rights Under the Universal Declaration of Human Rights in Indonesia - Kennedy, Alexander (Journal of Legal and Cultural Analytics, 2025)
This research examines the compatibility of Indonesia’s marriage laws with the Universal Declaration of Human Rights (UDHR), emphasizing issues of equality, freedom, and non-discrimination. Article 16 of the UDHR guarantees the universal right to marry based on free and full consent, without discrimination. However, Indonesia’s legal framework, particularly the 1974 Marriage Law, reflects the nation's dualist legal approach and its emphasis on particularity, whereby international human rights norms are selectively integrated into domestic law based on cultural and religious contexts. These restrictions include barriers to interfaith marriages, exclusion of non-religious individuals, and gender inequalities perpetuated by provisions such as polygamy. While the law preserves Indonesia’s cultural and religious diversity, it often conflicts with international human rights standards, highlighting tensions between universal norms and local practices. The study employs a juridical normative approach, analyzing legal instruments, court decisions, and international treaties to evaluate Indonesia's partial alignment with UDHR principles. Findings reveal systemic gaps, including discriminatory legal barriers for interfaith couples and women, inconsistent application of administrative provisions for marriage registration, and cultural practices like child marriages that undermine equality and autonomy. The research underscores the need for comprehensive reforms to harmonize Indonesia’s marriage laws with UDHR standards.